Management of Food Legume Pod borer and Aphids through Intercropping in Morocco in 2024 - Boulamtat, Rachid; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2024)
In Morocco, faba bean, kabuli chickpea and lentil are key crops in the cereal-based cropping system and provide food and incomes for small holder farmers. Pod borers and green pea aphids are key pests contributing to high yield gaps in the two crops because of weather variability. Farmers practice different cropping systems, but their ecological services are not well investigated. In this study, we investigated the roles of coriander intercropping as alternative management of pod borers in chickpea and green pea aphids on lentil. Results showed that Coriander intercropping with lentil reduced the mean number of aphids in intercropped plots compared with sole cropping. Likewise, chickpea intercropped with coriander showed reduced mean percent pod damage. Intercropping increased the number and diversity of natural enemies that affect the two pests. This innovation will be further demonstrated under farmer field conditions in 2024/25 cropping season.